The trialogue of Abrahamic religions: a plea for systematization of values = Trialogue agama Abrahamik: rayuan untuk sistematisasi nilai - Zein, Ibrahim Mohamed (International Islamic University Malaysia, 2012)
Judaism, Christianity, and Islam are known in intellectual discussion as Abrahamic religions. There have been efforts by some scholars of theses religions to initiate and continue trialogue among them. These efforts, however genuine they might be, are not free from flaws from rational and logical angles. In order to really make trialogue rationally meaningful and intellectually valuable there must be systemization of values as the basis for the task. Moses ibn Maimon (1135-1204), Martin Luther (1483-1546) and Ismail Ragi Al-Faruqi (1921-1986) have been selected in this paper to identify and highlight how sincerely they made their effort to develop principles of trialogue. The paper focuses on these principles: the realm of axiology is part and parcel of the metaphysical realm; the human being is the bridge between the physical and the metaphysical realm; in Islamic ethics the absolute values represent the attributes of God; there is a difference between a value in-it-self and its actualization in the material world; and monotheism is the only principle from which universality of ethics can be derived.